Exploring Reflective Teaching Practice of Indonesian EFL Teachers: A Case Study of Pre-Service Teachers’ Reflection in EFL Class - Istihari Istihari (Al Makki Publisher, 2023)
This research aimed at descriptively investigating pre-service teachers’ reflective teaching practices. The contents regarding analysis of the elements of reflection referred to the notion of reflective teaching proposed by Loughran (2006;1996). Four participants of EFL pre-service teachers doing teaching practice in two state secondary schools were involved in this study. Employing a case study design, data were collected through the participants’ reflective teaching journals and semi-structured interviews and were analyzed through inductive thematic analysis. The overall findings indicated that all elements of reflection were identified in the pre-service teachers’ reflective teaching journals although those elements did not emerge in sequence. Furthermore, the results showed that the issues that arose during teaching practice were related to learning management, knowledge management, classroom management, and language management. It is hoped that this study gives insight into the current debate concerning the rise of reflective teaching practice related to individual reflection during teaching practice and brings betterment in teacher education.